2017
DOI: 10.1111/aogs.13162
|View full text |Cite
|
Sign up to set email alerts
|

Fetal head circumference and subpubic angle are independent risk factors for unplanned cesarean and operative delivery

Abstract: Ultrasound assessment of fetal HC and maternal SPA after 36 weeks of gestation can identify a subset of women at higher risk of UOD during labor, for whom early planned delivery might be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 22 publications
1
13
0
2
Order By: Relevance
“…Some authors have observed that a large head circumference rather than birthweight is strongly associated with unplanned caesarean section and instrumental delivery [30], and very recently the relationship between SPA width and head circumference in the identification of women at risk of UOI has been confirmed [31].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors have observed that a large head circumference rather than birthweight is strongly associated with unplanned caesarean section and instrumental delivery [30], and very recently the relationship between SPA width and head circumference in the identification of women at risk of UOI has been confirmed [31].…”
Section: Discussionmentioning
confidence: 99%
“…(4) The vaginal delivery depends on fetal head circumference and maternal pelvic parameters like inter ischial diameter and subpubic angle. [21] The inclusion of these parameters may improve the accuracy. 5The confounding variable effect such as epidural analgesia needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation relates to the fact that we did not evaluate the measurement of transperineal subpubic angle and fetal head circumference in our study. Both parameters have been shown to be useful in predicting unplanned operative delivery before IOL in nulliparous women [27,28].…”
Section: Discussionmentioning
confidence: 99%